An Eddington ratio-driven origin for the LX − M* relation in quiescent and star-forming active galaxies. Issue 1 (22nd February 2022) - Carraro, Rosamaria; Shankar, Francesco; Allevato, Viola; Rodighiero, Giulia; Marsden, Christopher; Arévalo, Patricia; Delvecchio, Ivan; Lapi, Andrea
ABSTRACT: A mild correlation exists in active galaxies between the mean black hole accretion, as traced by the mean X-ray luminosity X > and the host galaxy stellar mass M*, characterised by a normalization steadily decreasing with cosmic time and lower in more quiescent galaxies. We create comprehensive semi-empirical mock catalogues of active black holes to pin down which parameters control the shape and evolution of the X > − M* relation of X-ray-detected active galaxies. We find that the normalization of the X > − M* relation is largely independent of the fraction of active galaxies (the duty cycle), but strongly dependent on the mean Eddington ratio, when adopting a constant underlying MBH − M* relation as suggested by observational studies. The data point to a decreasing mean Eddington ratio with cosmic time and with galaxy stellar mass at fixed redshift. Our data can be reproduced by black holes and galaxies evolving on similar MBH − M* relations but progressively decreasing their average Eddington ratios, mean X-ray luminosities, and specific star formation rates, when moving from the starburst to the quiescent phase. Models consistent with the observed X > − M* relation and independent measurements of the mean Eddington ratios are characterised by MBH − M* relations lower than those derived from dynamically measured local black holes. Our results point to the X > − M* relation as a powerful diagnostic to: (1) probe black hole–galaxy scaling relations and the level of accretion on to black holes; (2) efficiently break the degeneracies between duty cycles and accretion rates in cosmological models of black holes.